Digital health literacy among people with bipolar disorder in Germany – a cross-sectional survey - Kokwaro, Linda; Krüger, Helena; Stratmann, Dennis; Schulze, Daniel; Fürstenau, Daniel; Soekadar, Surjo R.; Lech, Sonia; Schreiter, Stefanie (Frontiers in Psychiatry, 2025)
BackgroundThis study assesses digital health literacy (DHL) among individuals with bipolar disorder (BD) in Germany, employing Sørensen’s Integrated Model of Health Literacy (SIMHL). According to SIMHL, health literacy is a dynamic construct influenced by demographic, structural, and situational factors. With increased adoption of digital health resources, often overlooked are the skills required to use these tools. This study aims to bridge this gap by examining overall patterns of DHL among individuals with BD and employing SIMHL to investigate DHL the role of associated structural, situational/clinical, and technical access factors.MethodsA cross-sectional online survey was conducted comprising 212 individuals with self-reported BD. DHL was assessed using the HL-DIGI instrument in addition to SIMHL factors including: structural (gender, employment status), situational (manic and depressive symptomatology), and technology use factors (use of health-related websites). Structural Equation Modeling (SEM) was used to model DHL as a latent variable.ResultsDHL followed a bimodal distribution, with participants clustering at either low (33.5%) or high (31.6%) levels. Evaluating reliability of online health information and using it to solve health-related tasks proved to be the most challenging. SEM demonstrated overall adequate model fit with higher DHL significantly associated with male gender, being employed and use of health-related websites.DiscussionIn line with SIMHL, DHL in individuals with BD is shaped by structural and access-related factors rather than illness severity. Gender, employment status, and engagement with health-related websites emerged as key correlates.ConclusionDHL in BD is not uniformly lower compared to the general population, underlining the feasibility of digital interventions as a promising pillar of care. At the same time, substantial heterogeneity highlights the need for routine DHL screening and tailored support for subgroups with lower skills. Future interventions and studies should systematically stratify by DHL level and target higher-order skills such as evaluating reliability and decision-making, in order to ensure equitable access and maximize the benefits of digital mental health care.